(untitled) (Journal of the College of Basic Education, 2022)
The theatrical performance, in general, is not complete except with the touch of the scenery that is compatible with the spirit of the work because it is the aesthetic element that participates in communicating the meaning of the show to the spectator. The show was in (the box theatre, the open theatre) and the extent of its impact on the recipient.With the passage of technical obsolescence in the use of the place of the show and its transformations from open spaces to closed spaces in what is called the box theater and the changes that occurred